The effect of Co electrodiffusion on the properties of YBaCuO superconductors - Dzhafarov, TD; Cevik, U (KLUWER ACADEMIC PUBL, 2001)
Diffusion over the temperature range 600-850 degreesC, electrodiffusion at 30 degreesC and effect of the Co substitution on crystalline structure and electrical characteristics of YBa2Cu3O7-y (YBaCuO) ceramic samples have been investigated by the energy dispersive X-ray fluorescence (EDX), X-ray diffraction (XRD), resistivity-temperature and current-voltage measurements. The temperature dependence of the cobalt diffusion coefficient (600-850 degreesC) via the grain boundaries has been described by the relation D=5.1 x 10(-4) exp (-1.12/kT). It is shown that the Co- doping of YBaCuO causes depression of the critical temperature and the critical current density. At the room temperature Co migrates in d.c. electric field preferentially in the form of positively charged ions with an effective charge q approximate to +0.6. Electrodiffusion-stimulated orthorhombic- tetragonal transition, decrease in critical temperature and critical current density and change of the form of resistivity-temperature dependence are discovered. (C) 2001 Kluwer Academic Publishers.
Keywords: SUBSTITUTION; TEMPERATURE; DIFFUSION; YBA2CU3O7-DELTA; FE; ZN; NI; Engineering; Materials Science; Physics